Conservation and reproductive activity of Olive Ridley sea turtle (Lepidochelys olivacea) in solitary nesting beach Punta Banco, South Pacific of Costa Rica: Management recommendations from sixteen years of monitoring. - Viejobueno Muñoz, Sandra; Arauz, Randall (Revista de Biología Tropical, 2015)
Sea turtle nesting activity was monitored in Punta Banco, South Pacific Costa Rica uninterruptedly for sixteen years, accompanied by conservation activities such as nest relocation in hatcheries. Hatching success evaluations were held for “in situ” and relocated nests. We hereby evaluate the reproductive biology of the olive ridley sea turtle (Lepidochelys olivacea), by far the most common turtle sea turtle nesting in Punta Banco (98% of observed turtles). Daily monitoring of nesting activities was held every year from July to December, from 1996 to 2011. We tagged a total of 1 239 turtles and recorded 4 130 nesting events. The number of recorded nesting events per nesting season ranged from 239 in 1996 to 402 in 1999, whereas the number of observed females ranged from 18 in 1996 to 146 in 1999. Nesting females had an average curved carapace length of 66.8cm and an average curve carapace width of 70.7cm. The average clutch size was 96.7, with an observed frequency of 1.07 nests/female and an nesting interval of 19.95 days. Hatching success of “in situ” nests was 61.38%, whereas hatching success for nests relocated into hatcheries was 77.9%. The L. olivacea population in Punta Banco beach displays a a positive trend.